A co-delivery system based on chlorin e6-loaded ROS-sensitive polymeric prodrug with self-amplified drug release to enhance the efficacy of combination therapy for breast tumor cells - Wang, Cui; Yang, Xiaoqing; Qiu, Haibao; Huang, Kexin; Xu, Qin; Zhou, Bin; Zhang, Lulu; Zhou, Man; Yi, Xiaoqing (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Recently, various combination therapies for tumors have garnered popularity because of their synergistic effects in improving therapeutic efficacy and reducing side effects. However, incomplete intracellular drug release and a single method of combining drugs are inadequate to achieve the desired therapeutic effect. Methods: A reactive oxygen species (ROS)-sensitive co-delivery micelle (Ce6@PTP/DP). It was a photosensitizer and a ROS-sensitive paclitaxel (PTX) prodrug for synergistic chemo-photodynamic therapy. Micelles size and surface potential were measured. In vitro drug release, cytotoxicity and apoptosis were investigated. Results: Ce6@PTP/DP prodrug micelles exhibited good colloidal stability and biocompatibility, high PTX and Ce6 loading contents of 21.7% and 7.38%, respectively. Upon light irradiation, Ce6@PTP/DP micelles endocytosed by tumor cells can generate sufficient ROS, not only leading to photodynamic therapy and the inhibition of tumor cell proliferation, but also triggering locoregional PTX release by cleaving the thioketal (TK) bridged bond between PTX and methoxyl poly (ethylene glycol). Furthermore, compared with single drug-loaded micelles, the light-triggered Ce6@PTP/DP micelles exhibited self-amplified drug release and significantly greater inhibition of HeLa cell growth. Conclusion: The results support that PTX and Ce6 in Ce6@PTP/DP micelles exhibited synergistic effects on cell-growth inhibition. Thus, Ce6@PTP/DP micelles represent an alternative for realizing synergistic chemo-photodynamic therapy.